2014
DOI: 10.1186/1476-4598-13-83
|View full text |Cite
|
Sign up to set email alerts
|

Effects of AKT inhibitor therapy in response and resistance to BRAF inhibition in melanoma

Abstract: BackgroundThe clinical use of BRAF inhibitors for treatment of metastatic melanoma is limited by the development of drug resistance. In this study we investigated whether co-targeting the MAPK and the PI3K-AKT pathway can prevent emergence of resistance or provide additional growth inhibitory effects in vitro.MethodsAnti-tumor effects of the combination of the BRAF inhibitor (BRAFi) dabrafenib and GSK2141795B (AKTi) in a panel of 23 BRAF mutated melanoma cell lines were evaluated on growth inhibition by an ATP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 41 publications
3
52
0
1
Order By: Relevance
“…Our result indicated that 100 nM of paclitaxel induced apoptosis of SKMEL-28 R about 3.3 folds, from 4.3% in the SKMEL-28 R control cells to 14.2% in paclitaxel-treated SKMEL-28 R cells (Figure 4g-h). Moreover, in previous studies, they showed that the combination of AKT inhibitors and BRAF inhibitors caused the decrease in melanoma development in cell lines and patients (Rebecca et al, 2012;Lassen et al, 2014). That means our result matches well with these previous studies to suggest that the simultaneous inhibitions of both AKT and BRAF could be beneficial for melanoma patients.…”
Section: Paclitaxel Reduced Cancer Characteristics and Induced Apoptosupporting
confidence: 82%
“…Our result indicated that 100 nM of paclitaxel induced apoptosis of SKMEL-28 R about 3.3 folds, from 4.3% in the SKMEL-28 R control cells to 14.2% in paclitaxel-treated SKMEL-28 R cells (Figure 4g-h). Moreover, in previous studies, they showed that the combination of AKT inhibitors and BRAF inhibitors caused the decrease in melanoma development in cell lines and patients (Rebecca et al, 2012;Lassen et al, 2014). That means our result matches well with these previous studies to suggest that the simultaneous inhibitions of both AKT and BRAF could be beneficial for melanoma patients.…”
Section: Paclitaxel Reduced Cancer Characteristics and Induced Apoptosupporting
confidence: 82%
“…Instead, many tumours carried pre-existing genetic variants, including RAC1, PTEN and AKT3 mutations that activate the PI3K-PTEN-AKT cascade. Consequently, although the sole activation of PI3K activity may not be sufficient to confer CombiDT resistance, we predict that PI3K activity modulates tumour responses to MAPK inhibitors and contributes to early resistance, and that combination MAPK and PI3K/AKT inhibition may be best administered upfront to delay the emergence of resistance 35 . Preclinical data have confirmed that PI3K activation (via NRAS mutations and receptor tyrosine kinase activation) diminished melanoma cell responses to combination BRAF and MEK inhibitors 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these data suggest that, in unselected patients with CombiDT failure, drug combinations involving PI3K/AKT inhibition (for example, NCT 01902173; ref. 35) may prove less successful than additional therapies inhibiting MAPK at multiple nodes, such as those targeting MEK, ERK and possibly CDK4 (NCT01777776, NCT01543698).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, acquired and innate oncogenic alteration in the PI3K/AKT signaling can explain the inefficiency of single pathway inhibition and the rationale for the concurrent targeting of both MAPK and PI3K/AKT pathways ( Figure 1) to counteract resistance and obtain beneficial long-term clinical effects. Several studies have demonstrated antitumor activity and pointed out synergistic effect of cotargeting MAPK and PI3K/AKT pathways in BRAF and NRAS mutant melanomas (22,24,31,(38)(39)(40).…”
Section: Co-targeting Of Mapk and Pi3k/akt Signaling Pathwaysmentioning
confidence: 99%